Macrophages: A communication network linking Porphyromonas gingivalis infection and associated systemic diseases - Lin, Jie; Huang, Dingming; Xu, Hongwei; Zhan, Fenghuang; Tan, XueLian (Frontiers in Immunology, 2022)
Porphyromonas gingivalis (P. gingivalis) is a Gram-negative anaerobic pathogen that is involved in the pathogenesis of periodontitis and systemic diseases. P. gingivalis has recently been detected in rheumatoid arthritis (RA), cardiovascular disease, and tumors, as well as Alzheimer’s disease (AD), and the presence of P. gingivalis in these diseases are correlated with poor prognosis. Macrophages are major innate immune cells which modulate immune responses against pathogens, however, multiple bacteria have evolved abilities to evade or even subvert the macrophages’ immune response, in which subsequently promote the diseases’ initiation and progression. P. gingivalis as a keystone pathogen of periodontitis has received increasing attention for the onset and development of systemic diseases. P. gingivalis induces macrophage polarization and inflammasome activation. It also causes immune response evasion which plays important roles in promoting inflammatory diseases, autoimmune diseases, and tumor development. In this review, we summarize recent discoveries on the interaction of P. gingivalis and macrophages in relevant disease development and progression, such as periodontitis, atherosclerosis, RA, AD, and cancers, aiming to provide an in-depth mechanistic understanding of this interaction and potential therapeutic strategies.